Circulating Biologically Active Adrenomedullin Predicts Organ Failure and Mortality in Sepsis - Kim, Hanah (Ann Lab Med, 2019)
BACKGROUND: Sepsis is a life-threatening organ dysfunction caused by a dysregulated host response to infection. Biologically active adrenomedullin (bio-ADM) is an emerging biomarker for sepsis. We explored whether bio-ADM concentration could predict severity, organ failure, and 30-day mortality in septic patients. METHODS: In 215 septic patients (109 patients with sepsis; 106 patients with septic shock), bio-ADM concentration was measured at diagnosis of sepsis, using sphingotest bio-ADM (Sphingotec GmbH, Hennigsdorf, Germany) and analyzed in terms of sepsis severity, vasopressor use, and 30-day mortality. The number of organ failures, sequential (sepsis-related) organ failure assessment (SOFA) score, and 30-day mortality were compared according to bio-ADM quartiles. RESULTS: Bio-ADM concentration was significantly higher in patients with septic shock, vasopressor use, and non-survivors than in patients with solitary sepsis, no vasopressor use, and survivors, respectively (all P<0.0001). Bio-ADM quartiles were associated with the number of organ failures (P<0.0001), as well as SOFA cardiovascular, renal, coagulation, and liver subscores (all P<0.05). The 30-day mortality rate showed a stepwise increase in each bio-ADM quartile (all P<0.0001). Bio-ADM concentration and SOFA score equally predicted the 30-day mortality (area under the curve: 0.827 vs 0.830). CONCLUSIONS: Bio-ADM could serve as a useful and objective biomarker to predict severity, organ failure, and 30-day mortality in septic patients.